Training of child and adolescent psychiatry fellows in autism and intellectual disability. (May 2014) - Marrus, Natasha; Veenstra-VanderWeele, Jeremy; Hellings, Jessica A; Stigler, Kimberly A; Szymanski, Ludwik; King, Bryan H; Carlisle, L Lee; Cook, Edwin H; Pruett, John R
Patients with autism spectrum disorders and intellectual disability can be clinically complex and often have limited access to psychiatric care. Because little is known about post-graduate clinical education in autism spectrum disorder and intellectual disability, we surveyed training directors of child and adolescent psychiatry fellowship programs. On average, child and adolescent psychiatry directors reported lectures of 3 and 4 h per year in autism spectrum disorder and intellectual disability, respectively. Training directors commonly reported that trainees see 1–5 patients with autism spectrum disorder or intellectual disability per year for outpatient pharmacological management and inpatient treatment. Overall, 43% of directors endorsed the need for additional resources for training in autism spectrum disorder and intellectual disability, which, coupled with low didactic and clinical exposure, suggests that current training is inadequate.